Clinical Implications of IL-32, IL-34 and IL-37 in Atherosclerosis: Speculative Role in Cardiovascular Manifestations of COVID-19 - Law, Ching Chee; Puranik, Rajesh; Fan, Jingchun; Fei, Jian; Hambly, Brett D.; Bao, Shisan (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerosis, which is a primary cause of cardiovascular disease (CVD) deaths around the world, is a chronic inflammatory disease that is characterised by the accumulation of lipid plaques in the arterial wall, triggering inflammation that is regulated by cytokines/chemokines that mediate innate and adaptive immunity. This review focuses on IL-32, -34 and -37 in the stable vs. unstable plaques from atherosclerotic patients. Dysregulation of the novel cytokines IL-32, -34 and -37 has been discovered in atherosclerotic plaques. IL-32 and -34 are pro-atherogenic and associated with an unstable plaque phenotype; whereas IL-37 is anti-atherogenic and maintains plaque stability. It is speculated that these cytokines may contribute to the explanation for the increased occurrence of atherosclerotic plaque rupture seen in patients with COVID-19 infection. Understanding the roles of these cytokines in atherogenesis may provide future therapeutic perspectives, both in the management of unstable plaque and acute coronary syndrome, and may contribute to our understanding of the COVID-19 cytokine storm.